1991
DOI: 10.1111/j.1471-4159.1991.tb08242.x
|View full text |Cite
|
Sign up to set email alerts
|

Saturable Transport of Manganese(II) Across the Rat Blood‐Brain Barrier

Abstract: Unanesthetized adult male rats were infused intravenously with solutions containing 54Mn (II) and one of six concentrations of stable Mn(II). The infusion was timed to produce a near constant [Mn] in plasma for up to 20 min. Plasma was collected serially and on termination of the experiment, samples of CSF, eight brain regions, and choroid plexus (CP) were obtained. Influx of Mn (JMn) was calculated from uptake of 54Mn into tissues and CSF at two different times. Plasma [Mn] was varied 1,000-fold (0.076-78 nmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 34 publications
8
84
0
Order By: Relevance
“…On the other hand, we cannot exclude the possibility that the increased accumulation of manganese in the functionally activated brain regions -at least to some extent -results from an accelerated direct transport of manganese from the blood stream across BBB of the cerebral capillaries via a non-specific metal transporters (Takeda, 2003). It has been shown that at high plasma concentrations transport across the choroid plexus is more prevalent, while at normal plasma concentrations the transport across cerebral capillaries dominates (Murphy et al, 1991;Rabin et al, 1993); the latter could be true in case of low doses of manganese. More experiments will be required to clarify the extent to which MEMRI is independent from neurovascular effects.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, we cannot exclude the possibility that the increased accumulation of manganese in the functionally activated brain regions -at least to some extent -results from an accelerated direct transport of manganese from the blood stream across BBB of the cerebral capillaries via a non-specific metal transporters (Takeda, 2003). It has been shown that at high plasma concentrations transport across the choroid plexus is more prevalent, while at normal plasma concentrations the transport across cerebral capillaries dominates (Murphy et al, 1991;Rabin et al, 1993); the latter could be true in case of low doses of manganese. More experiments will be required to clarify the extent to which MEMRI is independent from neurovascular effects.…”
Section: Discussionmentioning
confidence: 95%
“…The ability of manganese to cross the BBB following systemic administration (Murphy et al, 1991;Rabin et al, 1993), enter excitable cells via voltage-gated Ca 2+ channels (Drapeau and Nachshen, 1984;Lin and Koretsky, 1997;Narita et al, 1990;Silva et al, 2004) and accumulate in the activated brain regions gives the unique opportunity to use MEMRI for the whole-brain functional mapping. Exposure to subtoxic levels of manganese extends the application of this method to behaving animals.…”
Section: Application Of Memri For Whole-brain Mapping In Behaving Animentioning
confidence: 99%
“…It appears that facilitated diffusion (Rabin et al, 1993), active transport (Murphy et al, 1991;Aschner and Gannon, 1993;Rabin et al, 1993), DMT-1-mediated transport (Erikson et al, 2004a;Garrick et al, 2003), ZIP8-, store-operated calcium channels as well as transferrin (Tf)-dependent transport (Aschner and Gannon, 1993) mechanisms are all involved in shuttling Mn across the BBB. Although non-protein-bound Mn enters the brain more rapidly than Tfbound Mn (Murphy et al, 1991;Rabin et al, 1993), it is unclear as to which form represents the predominant mechanism of transport in situ.…”
Section: Other Potential Transporters Of Brain Mnmentioning
confidence: 99%
“…When the plasma concentration of Mn 2þ increases, the influx of Mn 2þ into the ventricular CSF is 100 times faster than the influx into brain tissue protected by BBB. In other words, the blood-CSF barrier seems to be more permeable to Mn 2þ ions than the BBB, so that the uptake into the central nervous system via the choroid plexus becomes the predominant form (71,72). As the ependyma, the lining of the cerebral ventricles, regulates the transport of ions including Ca 2þ and Mn 2þ across the CSF-brain barrier into the interstitial fluid, brain regions adjacent to the ventricles may receive significant amounts of Mn 2þ not only from the cerebral capillaries but also via the ventricular CSF.…”
Section: Molecular Mechanisms Of Memrimentioning
confidence: 99%
“…It may therefore be concluded that the predominant contribution to the axonal transport of Mn 2þ ions stems from the fast process. After transport along the microtubules to the synaptic cleft, the Mn 2þ is released at the synaptic cleft, where it can be taken up by the next neuron in the circuit (71,72,86,87). Quite interestingly, it has been shown that neurons that have been preloaded with Mn 2þ co-release the ion with glutamate upon stimulation, indicating the possibility that Mn 2þ is transported within synaptic vesicles (88).…”
Section: Molecular Mechanisms Of Memrimentioning
confidence: 99%